Molecular and phylogenetic analysis of herpesviruses in endangered free-ranging cervids of Chile: ovine gammaherpesvirus-2—A novel threat to wild and domestic animal health in Chilean Patagonia - Hidalgo-Hermoso, Ezequiel; Cabello, Javier; Lopez, Rodrigo; Vergara-Wilson, Vicente; Vera, Frank; Valencia, Carola; Sanchez, Carlos; Celis, Sebastian; Silva, Alejandra; Cariñanos, Aintzane; Barria, Ismael; Vicencio, Rocio; et al. (Frontiers in Veterinary Science, 2024)
Introduction Herpesvirus infections have been highlighted as emerging diseases affecting wildlife health and the conservation of several taxa. Malignant catarrhal fever (MCF) and infectious keratoconjunctivitis (IKC) are two viruses that infect wild ruminants. Nevertheless, epidemiological data on herpesviruses in South American wild ruminants are limited. An outbreak of caprine gammaherpesvirus-2 (CpHV-2) that recently was suspected as the cause of MCF in southern pudus (Pudu puda) prompted the need to conduct molecular screenings in Chilean cervids to understand the epidemiology of herpesviruses. The aim of this study was to determine the occurrence and genetic diversity of herpesviruses in free-ranging cervids from Chile. Methods Herpesvirus infection was assessed in antemortem blood samples (n = 86) from pudus (n = 81) and huemuls (Hippocamelus bisulcus) (n = 5), as well as postmortem samples of spleen (n = 24) and lung (n = 3) from pudus, using a nested pan-herpesvirus PCR assay. Results Combining all suitable sample types, DNA of pudu gammaherpesvirus-1 was detected in five pudues and five huemuls, with an overall prevalence of 9.90% (n = 10/101; 95% CI = 5.11–17.87%). One pudu tested positive for ovine gammaherpesvirus-2 (n = 1/96; 1.04%; 95% CI = 0.05–6.49%), and one pudu tested positive for a Macavirus sequence with 98.63 similarity to ovine gammaherpesvirus-2 (n = 96; 1.04%; 95% CI = 0.05–6.49%). Discussion To the best of our knowledge, this is the first report of a herpesvirus in huemul and of ovine gammaherpesvirus-2 in Chile. Our results also confirm the active circulation of herpesvirus in free-ranging cervids in Chilean Patagonia, and as such, MCF should be considered as a possible cause of disease in free-ranging Chilean pudus and livestock species. Further research is necessary to develop a plan of systematic monitoring (serological and pathological screening) of herpesviruses in Chilean wild and domestic ruminants to understand their diversity and impact on animal health and conservation.